Management effectiveness positively influences forest conservation outcomes in protected areas. (August 2021) - Powlen, Kathryn A.; Gavin, Michael C.; Jones, Kelly W.
Abstract: Understanding the factors that drive protected area outcomes is critical to increase the success of global conservation efforts. Until recently, our understanding of the influence of management effectiveness has been restricted by the limited availability of standardized management data and study design limitations of prior evaluations. Here we use a quasi-experimental matching approach to test the influence of management effectiveness on forest cover change inside 46 protected areas in Mexico. We test the influence of five management categories, including context and planning, administration and finance, use and benefits, governance and social participation, and management quality, as well as an overall effectiveness score, using a subgroup analysis and an interaction term in post-matching multiple linear regression. Our results show that protected areas with higher management effectiveness have a greater effect on reducing deforestation compared to those with low management effectiveness, but that both types of protected areas experience less forest loss compared to similar unprotected areas. We find this trend in all five of the management categories and the overall score, with administration and finance scores having the greatest effect on forest loss outcomes. Our findings suggest careful design and planning, effective participation from multiple stakeholders and equal sharing of benefits, and sufficient human and financial capital can improve the effectiveness of protected areas in preventing forest loss. Highlights: Protected areas (PAs) reduce forest loss across Mexico. PAs with higher management effectiveness scores prevent more forest loss. Human and financial capacity have the strongest relationship with PA outcomes.